WEIGHT AND PHYSICAL COMPOSITION OF QUAIL CARCASS WHICH IS GIVEN OF DRAGON FRUIT PEEL JUICE THROUGH DRINKING WATER - C. M., Christian; Dewi, G. A. M. K.; Umiarti, A. T. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the physical composition of quail carcasses given the level of dragon fruit peel juice through drinking water. This research was conducted for 5 weeks in Banjar Babakan, Selemadeg Village, Tabanan Regency, Bali. The design used was Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications where each replication consisted of 5 quails. The treatments were drinking water without dragon fruit peel juice (A), drinking water given 3% dragon fruit peel juice (B), drinking water given 4% dragon fruit peel juice (C), drinking water given 5% fruit peel juice dragon (D). The variables observed included carcass weight, meat weight, bone weight, skin weight and fat. The results showed that drinking water given 4% and 5% dragon fruit peel juice resulted in significantly different carcass weight (P<0.05) than quail given drinking water without dragon fruit peel juice. Giving drinking water 3%, 4% and 5% can produce meat weight, bone weight, skin weight and fat which are not significantly different (P>0.05) than quail given drinking water without dragon fruit peel juice. Based on the results of the study, it can be concluded that the administration of dragon fruit peel juice at levels of 4% and 5% can increase carcass weight but has not been able to increase the physical composition of the carcass in the form of meat, bone, skin and fat weight, while the 3% level has not been able to increase carcass weight and composition. physical carcass of quail aged 1-5 weeks. Keywords: Quail, physical carcass meat, dragon fruit skin juice